2014
DOI: 10.4236/wja.2014.43039
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Outcomes of Women Started on Antiretroviral Therapy during Pregnancy before and after the Implementation of Option B+ in Malawi: A Retrospective Chart Review from Three Facilities

Abstract: Objective To compare one-year outcomes of women started on antiretroviral therapy (ART) during pregnancy in the pre-Option B+ era to those in the Option B+ era. Methods A retrospective chart review was performed at three sites in Malawi. Women were included in the ‘pre-Option B+’ cohort if they started ART during pregnancy for a CD4 count < 350 cells/mm3 or WHO 3/4 condition and in the ‘Option B+’ cohort if they started ART during pregnancy regardless of CD4 count or clinical stage. One-year outcomes were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 6 publications
2
26
0
Order By: Relevance
“…In addition, the introduced PMTCT interventions have been effective in preventing infection in newborns, as other researchers have previously demonstrated [14]. Like other researchers [15], we found providers believed that antiretroviral combination therapy led to dramatic improvements in the survival of women living with HIV.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, the introduced PMTCT interventions have been effective in preventing infection in newborns, as other researchers have previously demonstrated [14]. Like other researchers [15], we found providers believed that antiretroviral combination therapy led to dramatic improvements in the survival of women living with HIV.…”
Section: Discussionsupporting
confidence: 65%
“…Very few studies have shown this relationship, but a study carried out among Malawian women described that feeling pressure to initiate ART immediately at the time of HIV diagnosis with little or no support in health-related decision-making was significantly associated with poor adherence [22,23]. …”
Section: Discussionmentioning
confidence: 99%
“…There is substantial body of literature from elsewhere on the effectiveness of the PMTCT programme in reducing transmission from mother to child, but data from Africa about the operational effectiveness of Option B+ in the PMTCT are sparse (17,(19)(20)(21)(22)(23)(24)(25)(26)(27). Particularly in Zambia the effectiveness of option B+ has not been evaluated, as far as we are aware, thereby raising concerns on its effectiveness in the elimination of MTCT.…”
Section: (Regardless Of Clinical Stage) Option a Regimen Included Aztmentioning
confidence: 99%